2022
DOI: 10.1002/chem.202104420
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Aminoferrocene Derivatives Inducing Production of Mitochondrial Reactive Oxygen Species

Abstract: Elevated levels of reactive oxygen species (ROS) and deficient mitochondria are two weak points of cancer cells. Their simultaneous targeting is a valid therapeutic strategy to design highly potent anticancer drugs. The remaining challenge is to limit the drug effects to cancer cells without affecting normal ones. We have previously developed three aminoferrocene (AF)‐based derivatives, which are activated in the presence of elevated levels of ROS present in cancer cells with formation of electron‐rich compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…We detected no signs of tumors, indicating that these animals were completely cured (Figure S62, Supporting Information). This is an exciting result, which we have previously never observed for other Fe-containing drugs. , Due to the excellent performance in the standard tumor model, we have also investigated its effects in the second, more challenging NK/Ly model, in which the cancer cells grow in the abdomen as ascites. This cancer is very aggressive, and untreated animals have a half-life of only 18 days.…”
Section: Resultsmentioning
confidence: 99%
“…We detected no signs of tumors, indicating that these animals were completely cured (Figure S62, Supporting Information). This is an exciting result, which we have previously never observed for other Fe-containing drugs. , Due to the excellent performance in the standard tumor model, we have also investigated its effects in the second, more challenging NK/Ly model, in which the cancer cells grow in the abdomen as ascites. This cancer is very aggressive, and untreated animals have a half-life of only 18 days.…”
Section: Resultsmentioning
confidence: 99%
“…The ascites was isolated from the peritoneal cavity of mice with a syringe. This cellular suspension was then centrifuged at 1500 g to separate the cells and acellular supernatant, which was referred to as ascites fluid . After sedimentation, the cells were washed twice in PBS and used for analysis, while the ascites fluid was dissolved to 50% v / v in PBS due to the technical need for equalizing the volume in all samples.…”
Section: Methodsmentioning
confidence: 99%
“…This cellular suspension was then centrifuged at 1500g to separate the cells and acellular supernatant, which was referred to as ascites fluid. 39 After sedimentation, the cells were washed twice in PBS and used for analysis, while the ascites fluid was dissolved to 50% v/v in PBS due to the technical need for equalizing the volume in all samples. Additionally, some wells were supplemented with a protease inhibitor cocktail at a final concentration of 0.5% (Sigma-Aldrich P8340).…”
Section: Fluorescence Of Squaraine Dyes Upon An Interaction With Biol...mentioning
confidence: 99%
“…Ferrocene-Capped Tripeptides 23-30 [35] Previous observations prompted us to investigate the use of ferrocene as a CD probe for the detection of screw sense preferences of short peptide sequences, for which we synthesized all eight stereoisomers of Boc-Pro-Pro-Ala-NH-Fn (23)(24)(25)(26)(27)(28)(29)(30) [35]. This investigation was inspired by early work by Toniolo [106] and his p-bromobenzamido chromophore and Clayden's dibenzazepinylurea [107], which were used as N-terminally covalently bound CD probes for determination and quantification of the screw sense preferences of peptide sequences.…”
Section: C-terminalmentioning
confidence: 99%
“…N-alkylaminoferrocene-based prodrugs, activated under cancerspecific conditions, i.e., a high ROS concentration, were able to reduce the mitochondrial membrane potential, but also showed low efficacy and high toxicity [21][22][23]. Structural optimization led to aminoferrocene derivatives that are able to generate mitochondrial ROSs only in cancer cells, and therefore have anticancer activity in vivo [24]. It has been shown that the self-immolative amphiphilic poly(ferrocenes) containing aminoferrocene side chains are triggered by acidic tumor conditions; the aminoferrocene moiety reacts to give Fe 2+ , which can catalyze the conversion of intracellular H 2 O 2 to highly reactive ˙OH, leading to the oxidative stress of tumor cells [25].…”
Section: Introductionmentioning
confidence: 99%